Features of art reconstruction in the historical novel (Eurasian Journal of Philology Science and Education, 2016)
In article the problem of art reconstruction of historical reality in Mukhtar Magauin’s novel «Time of Troubles» is considered. In creation of a work of art the main place belongs to the identity of the writer. There is the whole complex of sources literary, philosophical, historical which impact on the writer happens in two main directions: the first of them is connected with literary, philosophical traditions; the second – with primary sources.  Author’s subjectivity in art reconstruction of historical events in the novel doesn’t contradict vital logic. Art reconstruction of documents is characterized as one of the principles of typification in the historical novel. Documentary certificates are used by the writer as a basis for a reconstruction and identification of moral sense of historical events, characteristics of heroes, confirmations of the author’s concept of images of a historical era.
Keywords: art reconstruction; historical novel; history truth; art fiction